Symbolic Interaction in Interpreting "Pengajian" among Rural and Urban Communities - Dira Ligiar; Abd. Hadi; Imron Mustofa (Journal of Islamic and Social Studies, 2025)
This study aims to explore and understand the differences in symbolic interactions that occur in the context of recitation between villagers and urban communities. Recitation is an Islamic tradition that is widely known to the public and is also popular in Indonesia. This tradition has its own very deep and touching meaning for the congregation in Indonesia, both rural and urban communities. Recitation becomes a space for learning and sharing Islamic knowledge, Islamic history, as well as becoming an intermediary or bridge to strengthen ties of brotherhood and solidarity between Muslims. Through a qualitative approach with a comparative study, this research identifies certain symbols or meanings related to recitation and explores how social and cultural backgrounds influence individual perceptions of science councils in both social contexts. Symbolic interactions in science councils in villages and cities reflect the socio-cultural conditions that exist or are occurring in both communities. Village recitations focus more on basic religious knowledge and have an informal atmosphere with a more naturalistic, simple nature and better reflect harmony between Muslims. Meanwhile, Koran studies in cities focus more on contemporary issues and have a formal atmosphere that reflects the complexity and dynamics of urban society. It focuses more on scientific studies and ignores solidarity and harmony between Muslims